Dynamics of virus-receptor interactions in virus binding, signaling, and endocytosis - Boulant, Steeve; Stanifer, Megan; Lozach, Pierre-Yves (Viruses, 2015)
During viral infection the first challenge that viruses have to overcome is gaining access to the intracellular compartment. The infection process starts when the virus contacts the surface of the host cell. A complex series of events ensues, including diffusion at the host cell membrane surface, binding to receptors, signaling, internalization, and delivery of the genetic information. The focus of this review is on the very initial steps of virus entry, from receptor binding to particle uptake into the host cell. We will discuss how viruses find their receptor, move to sub-membranous regions permissive for entry, and how they hijack the receptor-mediated signaling pathway to promote their internalization.
Gesehen am 25.04.2017